Decreased expression of AZGP1 is associated with poor prognosis in primary gastric cancer. - Chun-yu Huang; Jing-jing Zhao; Lin Lv; Yi-bing Chen; Yuan-fang Li; Shan-shan Jiang; Wei Wang; Ke Pan; Yan Zheng; Bai-wei Zhao; Dan-dan Wang; Yong-ming Chen; et al. (PLoS ONE, 2013)
BACKGROUND: 2-Zinc-glycoprotein 1 (AZGP1) is a multidisciplinary protein that participates in many important functions in the human body, including fertilization, immunoregulation and lipid mobilization. Recently, it has been shown that AZGP1 is also involved in carcinogenesis and tumor differentiation. In this study, we investigated the expression levels and prognostic value of AZGP1 in primary gastric cancers. METHODS AND RESULTS: We examined the expression of AZGP1 in 35 paired cancerous and matched adjacent noncancerous gastric mucosa tissues by real-time quantitative RT-PCR (qRT-PCR) and western blotting. Furthermore, we analyzed AZGP1 expression in 248 patients who underwent resection procedures between 2005 and 2007 using immunohistochemistry. The relationships between the AZGP1 expression levels, the clinicopathological factors, and patient survival were investigated. AZGP1 expression was significantly reduced at both the mRNA (P = 0.023) and protein levels (P = 0.019) in tumor tissue samples, compared with expression in matched adjacent non-tumor tissue samples. The immunohistochemical staining data showed that AZGP1 expression was significantly decreased in 52.8% (131/248) of gastric adenocarcinoma cases. Clinicopathological analysis showed that the reduced expression of AZGP1 was significantly correlated with tumor location (P = 0.011), histological grade (P = 0.005) and T stage (P = 0.008). Kaplan-Meier survival curves revealed that the reduced expression of AZGP1 was associated with a poor prognosis in gastric adenocarcinoma patients (P = 0.009). Multivariate Cox analysis identified AZGP1 expression was an independent prognostic factor for overall survival of gastric adenocarcinoma patients (HR = 1.681, 95% CI = 1.134-2.494, P = 0.011). CONCLUSIONS: Our study suggests that AZGP1 might serve as a candidate tumor suppressor and a potential prognostic biomarker in gastric carcinogenesis.